Killer bees - Hines, Marcia frey50 (Mankato, Minn. : RiverFront Books, 1998)
Details the characteristics, habitat, and life cycle of the Africanized honeybee, sometimes referred to as the killer bee.
Keywords: Africanized honeybee; Africanized honeybee; Bees